Uso de algoritmos genéticos na otimização do sistema de coleta do palhiço de cana-de-açúcar - Oliveira, Guilherme Gomes Neves de [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The Brazilian government has convinced the world that ethanol deriving from sugar cane is a promissory means of sustainable fuel for vehicles. There is a great growth of ex vehicles , i.e, run both by ethanol and gasoline, due to competent automotive industries and e cient alcohol production technology. In 2009 and 2010 the ethanol production was 25.7 billion liters and 53.8% of sugar cane production was destined to alcohol production. Nevertheless, the sugar production also derived from sugar cane should increase in 2011. Brazil produced 33 million tons of sugar in the last harvest. With sugar cane on the rise production is arising new environmental problems. The harvest using mechanized cut besides improving the logistic transportation system leaves the generating residue in the eld. This residue is a mixture of straw, leavings and scrap of sugar cane named sugar cane crop residue and corresponds to 30% of biomass and can be burned and produce electricity by cogeneration. But the transport the sugar cane crop from the eld is expensive due costs involved in the transport system. This work aims to propose a formulation for the bales collecting problem from sugar cane eld to mill that minimize the costs involved in the transport system. The computational tests use the C++ language and an algorithm based on genetic algorithms techniques

A preocupação com o meio ambiente e as novas leis ambientais tem feito com que empresas produtoras de cana-de-açúcar busquem reduzir a queima do canavial e melhorar as formas de corte e colheita da cana crua. O corte mecanizado d a origem ao palhiço de cana-de-açúcar, formando um ambiente propício para o surgimento de pragas e para o atraso no brotamento da cana. V arias usinas t em transportado o palhi co do campo para o centro de processamento, no intuito de serem reaproveitados como fonte de energia. Por em a inser c~ao deste processo na colheita gera grandes di culdades as usinas, no que diz respeito a tecnologia de coleta e ao aproveitamento do palhi co, devido ao custo envolvido no sistema de transporte. Para reduzir tais problemas, prop~oe-se neste trabalho, uma formula c~ao do problema de coleta dos fardos de palhi co de cana-de-a c ucar do campo ao centro de processamento para a gera c~ao de energia, como um problema de transporte, que busca minimizar a dist ancia percorrida pelos ve culos evitando a forma c~ao de las de carga e descarga na usina. Para resolver o problema foram estudadas metaheur sticas baseadas no algoritmo gen etico
Keywords: Computação; Cana-de-açúcar - Transporte; Algoritmos genéticos